-5n-3=-13

Simple and best practice solution for -5n-3=-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5n-3=-13 equation:



-5n-3=-13
We move all terms to the left:
-5n-3-(-13)=0
We add all the numbers together, and all the variables
-5n+10=0
We move all terms containing n to the left, all other terms to the right
-5n=-10
n=-10/-5
n=+2

See similar equations:

| -4(m-5)+6=18 | | 3(x-3)^2=144 | | -20x+2=-30-15 | | 8/9=a/36 | | (11x+3)°=(14x+20)° | | w+7=26 | | 5x-16=-91 | | 938402394023n=10n | | 938402394023n=11n | | 15x^2-1x4-54=0 | | 15x^2-x4-54=0 | | 27=b4.5 | | 23-2v=7(v+1)-v | | 13x-24=212 | | 3x-10+4x=2(x-4)+9x | | -5-3x+8=30 | | 3x-10=5x+40 | | 5x+8x+9-36=0 | | +4x=+40 | | r/4− 4=1 | | m/4+36=41 | | 47−0u=25 | | B=3.5h=6 | | 47−u=25 | | j+40=-10+7 | | r/9+75=79 | | -122+7j=-8j-2 | | 17-4h=59 | | 59=4h−17 | | 2x-8/x=6 | | 3=×-y | | 27=46+2x-4 |

Equations solver categories